Analisis Sektor Unggulan pada Perekonomian Kabupaten Pasuruan - Nur Latifah; Syamsul Huda (Al-Buhuts, 2023)
This study aims to determine which sectors are superior in Pasuruan Regency. The research used a quantitative descriptive approach using secondary data from the Gross Regional Domestic Product data for Pasuruan Regency and East Java Province in the 2017-2021 period. The analytical method used in this research is Location Quotient, Shift Share, Klassen Typology, Growth Ratio Model (MRP), Sectoral Contribution and Overlay analysis. Based on the results of the Location Quotient analysis, there are 3 basic sectors in Pasuruan Regency, while the results of the Shift Share analysis show that there are 7 sectors that encourage economic growth, 10 sectors that hinder economic growth and 4 sectors that have locational advantages in Pasuruan Regency and only 1 sector that is included in Quadrant I Based on the MRP analysis, 4 categories were obtained with 2 sectors included in classification I, 5 sectors included in classification II, 1 sector included in classification III and 9 sectors in classification IV. The biggest contribution in Pasuruan Regency is the Processing Industry sector and the Construction sector.